2011
DOI: 10.1007/s00270-011-0104-3
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Management of Postoperative Bile Leaks After Upper Gastrointestinal Surgery

Abstract: PTBD treatment is an effective therapy. PTBD treatment and additional CT-guided drainage of bilomas helped to reduce intraabdominal inflammation, as shown by reduction of inflammation parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 15 publications
2
22
1
1
Order By: Relevance
“…On the other hand, successful percutaneous management of bile leaks requires long therapy courses. An average duration of PTBD treatment of 6 weeks to 80 days has been reported [14,18]. As seen in our series, Onyx application for the management of bile leaks can shorten therapy courses substantially when combined with PTBD.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…On the other hand, successful percutaneous management of bile leaks requires long therapy courses. An average duration of PTBD treatment of 6 weeks to 80 days has been reported [14,18]. As seen in our series, Onyx application for the management of bile leaks can shorten therapy courses substantially when combined with PTBD.…”
supporting
confidence: 59%
“…In these situations, PTBD represents the approach of choice and provides a considerable reduction in repeated laparotomies. Recently, less invasive methods, such as PTBD combined with percutaneous drainage of bilomas, were successfully performed [14,15]. Surgical treatment is required when conservative endoscopic and radiological management fails and can be performed by liver resection, bile duct reconstruction or bilioenteric anastomosis [16,17].…”
mentioning
confidence: 99%
“…In patients with nondilated peripheral bile ducts at ultrasound, the puncture was performed under fluoroscopic guidance using cholangiography (obtained via the drainage catheter near the leak site or surgical T-tube). Furthermore, in some studies the puncture site was usually more central when the bile ducts were nondilated, as this facilitates the puncture [21,22,26]. Also, Funaki et al [17] reported a higher number of passes in patients with nondilated bile ducts.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this study encompassed the largest time span and sample size of its kind. Over the last 20 years a number of small studies in at least 10 patients also reported high technical success rates (91-100%), high clinical success rates (70-100%), and low major complication rates (0-13%) [8,19,21,22,25,26,30]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation